Brusselse werkloosheid balancerend tussen onaangepaste kwalificaties en verdringingseffect - Hervé Devillé (Brussels Studies, 2008)
This study presents an analysis of developments in the qualitative flexibility of the Brussels-Capital Region’s labour market since the start of the 1990s. This form of flexibility was studied simultaneously (rather than alternatively) from the standpoints of the incidences of skill mismatches and job competition between workers with different levels of education ((vertical) job competition) or overeducation on the probability of exiting unemployment for all levels of education. The conclusions reveal that despite the preponderance of mismatches for all levels of education, occupational downgrading has a growing and significant impact for all the higher levels of education, especially during business cycle lows. Boosting low-skilled employment selectively during such lows without boosting employment across the board will reduce the effectiveness of policies to combat the unemployment of people with low skills as high-skilled workers tend to spill over into less skilled employment segments.